A magnetic resonance imaging study of gastric motor function in patients with dyspepsia associated with Ehlers‐Danlos Syndrome‐Hypermobility Type: A feasibility study. Issue 9 (31st May 2017) - Menys, A.; Keszthelyi, D.; Fitzke, H.; Fikree, A.; Atkinson, D.; Aziz, Q.; Taylor, S. A.
Abstract: Background: The clinical use of Magnetic Resonance Imaging (MRI) for investigating gastric motor function in dyspepsia is limited, largely due to protocol complexity, cost and limited availability. In this study, we explore the feasibility of a sub 60‐minute protocol using a water challenge to assess gastric emptying, motility and accommodation in a cohort of Ehlers‐Danlos Syndrome‐Hypermobility type (EDS‐HT) patients presenting with dyspepsia. Methods: Nine EDS‐HT patients (mean age 33, range: 26‐50 all female) with a history of dyspepsia were recruited together with nine‐matched controls. Subjects fasted for 6 hours prior to MRI. A baseline anatomical and motility scan was performed after which the subjects ingested 300 mL water. The anatomical and motility scans were then repeated every 10 minutes to a total of 60 minutes. Gastric emptying time, motility, and accommodation were calculated based on the observations of two observers for each EDS‐HT subject and compared to their matched control using paired statistics. Key Results: Median motility increase following the water challenge was lower in EDS‐HT subjects (11%, range: 0%‐22%) compared to controls (22%, range: 13%‐56%), P =.03. Median gastric emptying time was non‐significantly decreased in EDS‐HT subjects (12.5 minutes, range: 6‐27) compared to controls (20 minutes, range: 7‐30), P =.15. Accommodation was non‐significantly reduced in EDS‐HT subjects (56% increase, range: 32%‐78%) compared to healthy controls (67% increase, range: 52%‐78%), P =.19. Conclusions & Inferences: This study demonstrates the feasibility of a water challenge MRI protocol to evaluate gastric physiology in the clinical setting. Motility differences between EDS‐HT and controls are worthy of further investigation. Abstract : Aberrant gastric motility, accommodation, transit time likely play a role in dyspepsia. MRI has the ability to quantitatively evaluate these processes but remains underused due the length of existing protocols and uncertainly regarding its role in the clinical care pathway. In this study, we propose a 60 minutes protocol using a water stimulus which reveals differences between Ehlers Danlos patients with dyspepsia and healthy matched controls.